Close your eyes [large type] - Johansen, Iris (Johansen, Iris. Kendra Michaels series., 2012)
The FBI has asked the help of Kendra Michaels whose astonishing powers of observation and analysis have made her a favorite of law enforcement agencies all across the country. She's not interested until Agent Lynch reveals that Agent Jeff Stedler -- Kendra's ex -- is missing and may have run directly into the path of a serial killer.